Bacteriophages Isolated From Turkeys Infecting Diverse Salmonella Serovars - Zhongjing Lu; John Marchant; Samantha Thompson; Henry Melgarejo; Dzhuliya Ignatova; Sandra Kopić; Rana Damaj; Hedy Trejo; Rodrigo Paramo; Ashley Reed; Fred Breidt; Fred Breidt; et al. (Frontiers in Microbiology, 2022)
Salmonella is one of the leading causes of foodborne illnesses worldwide. The rapid emergence of multidrug-resistant Salmonella strains has increased global concern for salmonellosis. Recent studies have shown that bacteriophages (phages) are novel and the most promising antibacterial agents for biocontrol in foods because phages specifically kill target bacteria without affecting other bacteria, do not alter organoleptic properties or nutritional quality of foods, and are safe and environmentally friendly. Due to the vast variation in Salmonella serotypes, large numbers of different and highly virulent Salmonella phages with broad host ranges are needed. This study isolated 14 Salmonella phages from turkey fecal and cecal samples. Six phages (Φ205, Φ206, Φ207, ΦEnt, ΦMont, and Φ13314) were selected for characterization. These phages were from all three families in the Caudovirales order. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) revealed that each phage had a unique structural protein profile. Each phage had a distinct host range. Φ207 and ΦEnt are both siphophages. They shared eight hosts, including seven different Salmonella serovars and one Shigella sonnei strain. These two phages showed different restriction banding patterns generated through EcoRI or HindIII digestion, but shared three bands from EcoRI digestion. ΦEnt displayed the broadest and very unusual host range infecting 11 Salmonella strains from nine serovars and three Shigella strains from two species, and thus was further characterized. The one-step growth curve revealed that ΦEnt had a short latent period (10 min) and relatively large burst size (100 PFU/infected cell). ΦEnt and its host showed better thermal stabilities in tryptic soy broth than in saline at 63 or 72°C. In the model food system (cucumber juice or beef broth), ΦEnt infection [regardless of the multiplicity of infections (MOIs) of 1, 10, and 100] resulted in more than 5-log10 reduction in Salmonella concentration within 4 or 5 h. Such high lytic activity combined with its remarkably broad and unusual host range and good thermal stability suggested that ΦEnt is a novel Salmonella phage with great potential to be used as an effective biocontrol agent against diverse Salmonella serovars in foods.